Hope, Optimism, Academic Flow, and Academic Engagement of Students in Online Learning - Yudi Suharsono; Siti Fatimah (Bisma The Journal of Counseling, 2025)
Online learning after the pandemic has brought new challenges, especially low student engagement due to distractions, decreased motivation, and increased academic workload. In addition, there is still limited research that simultaneously examines the role of positive psychological factors, namely hope, optimism, and flow experience, in comprehensively improving academic engagement. This study aims to analyze the relationship between hope, optimism, academic flow, and student academic engagement in online learning. The research design uses a correlational quantitative approach with multiple regression analysis. The participants consisted of 152 students. The instruments used included the Hope Scale, Optimism Scale, Academic Flow Scale, and Academic Engagement Scale. The results show that there is a significant simultaneous influence of expectations, optimism, and academic flow on academic engagement. Partially, these three variables also have a significant influence on academic engagement. These findings confirm that the higher the level of expectations, optimism, and flow experience of students, the higher their academic engagement in online learning. The implications of this study emphasize the importance of pedagogical strategies that foster optimism, stimulate expectations, and facilitate flow experiences to improve the quality of students' academic engagement.